Raumnutzungskonflikte am Nordrand des Ruhrgebietes - Hommel, Manfred (ERDKUNDE, 1984)
Despite some large coal mines, chemical plants, and power stations the Lippe Belt in the north of the Ruhr Coalfield has preserved its rural character till today. Within the context of the entire conurbation, the spatial functions of that part are mainly recreation and water supply, but are also, due to intensive suburbanization which is more and more affecting open space and its functions, increasingly residential. Land use planning in the Lippe Belt should therefore aim to preserve open space by restrictive zoning for residential use thereby impeding further suburbanization in that part of the conurbation. Due to its rich coal deposits and ample open space the Lippe Belt has a great industrial development potential, too, the realization of which has already started by sinking new shafts. This process, which seems to be inevitable for national economic reasons, is even more affecting open space and its functions. Land use planning should therefore aim at making further industrialization and particularly the expansion of coal mining in the Lippe Belt as compatible with open space and its functions as possible by protecting the ecologically most sensitive and most valuable areas and by taking care that where mining and industry use open space, it will be, if at all necessary, as land-saving as possible. Both development perspectives - further suburbanization and further industrialization - are discussed in detail, focussing on the latter, and measures are suggested at both the regional and the local level for monitoring spatial development in the Lippe Belt.